2022
DOI: 10.1155/2022/7608428
|View full text |Cite|
|
Sign up to set email alerts
|

Effectiveness of GnRH Antagonists and Agonists in Patients with Hormone-Sensitive Prostate Cancer: A Retrospective Study

Abstract: Objective. To assess the effectiveness of gonadotropin-releasing hormone (GnRH) antagonists and agonists in the treatment of patients with hormone-sensitive prostate cancer (HSPC), thus providing valid data support for their clinical treatment. Methods. We collected 52 and 65 HSPC patients treated with GnRH antagonists and agonists, respectively, in Tongji Hospital, Tongji Medical College of HUST between May 2019 and April 2021. Prostate-specific antigen (PSA) levels before and after treatment were recorded an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%